Learning to think strategically 4th edition - Sloan, Julia (Ascent Audio, 2020)
Strategic thinking has become a core competency for business leaders globally. Overused and under-defined, the term is often used interchangeably with other strategic management terms. This textbook delineates and defines strategic thinking as an advanced, conceptual cognitive capability, focusing on the nonlinear, divergent, a-rational, and informal nature of strategic thinking. This unique and practical book is an original primer of how successful strategists learn to think strategically.In this fourth edition, the author offers an expanded definition of strategic thinking based on critical theory. This book highlights the role of informal learning, underscores the relevance of engaging in the arts, and has global application for those tasked with making strategy in this rapidly changing world. Sloan presents a previously unexamined account of the relationship between strategic thinking and the learning process involved-taking learning from the academic to the everyday. New features include an expanded list of learning methods to develop strategic thinking, a more extensive look at global cultural perspectives of strategic thinking, and additional scenarios and case vignettes.